2021
DOI: 10.1101/2021.05.18.21257385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mask mandate and use efficacy for COVID-19 containment in US States

Abstract: Background: Containment of the COVID-19 pandemic requires evidence-based strategies to reduce transmission. Because COVID-19 can spread via respired droplets, many states have mandated mask use in public settings. Randomized control trials have not clearly demonstrated mask efficacy against respiratory viruses, but observational studies suggest greater mask compliance may be associated with lower infection rates. We hypothesized that statewide mask mandates and mask use are associated with lower COVID-19 case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The study evaluated the growth in COVID-19 cases post-mask mandate in non-mandate states compared to neighboring states with mask mandates. The study found no statistically significant difference in higher or lower transmission level growth rate of COVID-19 cases (Guerra & Guerra. 2021).…”
Section: Literature Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…The study evaluated the growth in COVID-19 cases post-mask mandate in non-mandate states compared to neighboring states with mask mandates. The study found no statistically significant difference in higher or lower transmission level growth rate of COVID-19 cases (Guerra & Guerra. 2021).…”
Section: Literature Reviewmentioning
confidence: 66%
“…Evidence in the literature suggested changing factors that was completely ignored in the literature resulted in the spread of misinformation about the effectiveness of facial coverings in response to the COVID-19 pandemic. Guerra and Guerra (2021) research that analyzed data from the Centers for Disease Control and Prevention, along with data from Institute for Health Metrics and Evaluation concluded mandates that required the use of masks were not associated with a reduction in the spread of COVID-19 at Print ISSN 2056-3620(Print) Online ISSN 2056-3639(Online) 13 @ECRTD-UK: https://www.eajournals.org/ Publication of the European Centre for Research Training and Development -UK statewide-level during COVID-19 surges. The study evaluated the growth in COVID-19 cases post-mask mandate in non-mandate states compared to neighboring states with mask mandates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other research, also undertaken in Spain, Marks et al examined various factors potentially affecting transmission of SARS-CoV-2, including mask use, reporting no observations relating to risk of transmission associated with reported mask usage, although the authors acknowledge the deficiencies in the analysis due to the lack of data on mask type [25]. A retrospective study on mask mandates and their use in the general population across the United States drew similar conclusions that these measures were not observed to be associated with reduced spread of SARS-CoV-2 [26]. Further, a report on a systematic review of 14 RCTs to evaluate the effectiveness of personal protective measures, including mask-wearing, found no evidence for a substantial effect of mask use on the transmission of laboratory-confirmed influenza [27].…”
Section: Efficacy Of Face Masks In Reducing Transmissionmentioning
confidence: 97%
“…Response often included restrictive population-wide measures, summarily called here non-pharmaceutical interventions (NPIs). However, here is little proof that most aggressive measures work much better than less disruptive, focused measures (e.g., Fögen, 2022;Guerra & Guerra, 2021; for reducing COVID-19 burden. Some adopted measures may even have severe negative consequences (for reviews see e.g., Panneer et al, 2022;Schippers, 2020).…”
Section: Introductionmentioning
confidence: 99%